Gender expression and gender identity in virtual reality: avatars, role-adoption, and social interaction in VRChat - Zhang, Jingyi; Juvrud, Joshua (Frontiers in Virtual Reality, 2024)
Utilizing unobtrusive observations and interviews within the VRChat platform, this research explored avatar choices, interactions, and full-body tracking (FBT) technology utilization as they related to users’ expressions and perceptions of gender in virtual reality (VR). The findings revealed that cultural background plays a significant role in shaping gender expression and perception. Results demonstrated the fluidity of gender expression in virtual environments, highlighting how users can challenge and subvert traditional gender norms, and the potential of virtual reality as a tool for experiential learning, fostering cross-cultural understanding, and promoting inclusive and diverse gender expressions. This study contributes to the emerging body of literature on virtual reality and gender, providing insights that can inform future research and technology development.